Interdyscyplinarność jako droga do konsiliencji i jej obecność w badaniach literaturoznawczych = Interdisciplinarity as a path to consilience and its presence in literary studiem - Saja, Krystian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
To the present day, the humanities are opposed to the modern paradigm of scientific research. t is widely understood interdisciplinarity. Divisions into narrow specializations led to the emergence of simple development paths in each of the disciplines. Meanwhile, exact sciences and the humanities are constantly intermingling. There is a natural, unavoidable interference between them. Expanding the nomenclature and background of humanities research methods to include issues and theories from exact sciences can prove extremely useful. The text is devoted to interdisciplinarity, considered in the humanities, with particular emphasis on literary studies.
Keywords: literature theory; literary studies; humanities sciences; science; consilience; interdisciplinarity; teoria literatury; literaturoznawstwo; nauki ścisłe; nauki humanistyczne; konsiliencja; interdyscyplinarność